Endocytosis and exocytosis of nanoparticles in mammalian cells - Oh N (Dove Medical Press, 2014)
Nuri Oh,1,2 Ji-Ho Park1–31Department of Bio and Brain Engineering, 2Institute for Optical Science and Technology, 3Institute for the NanoCentury, Korea Advanced Institute of Science and Technology (KAIST), Daejeon, Republic of KoreaAbstract: Engineered nanoparticles that can be injected into the human body hold tremendous potential to detect and treat complex diseases. Understanding of the endocytosis and exocytosis mechanisms of nanoparticles is essential for safe and efficient therapeutic application. In particular, exocytosis is of significance in the removal of nanoparticles with drugs and contrast agents from the body, while endocytosis is of great importance for the targeting of nanoparticles in disease sites. Here, we review the recent research on the endocytosis and exocytosis of functionalized nanoparticles based on various sizes, shapes, and surface chemistries. We believe that this review contributes to the design of safe nanoparticles that can efficiently enter and leave human cells and tissues.Keywords: drug delivery, endocytosis, exocytosis, cancer cell, macrophage, nanoparticle, toxicity